Claroideglomus etunicatum enhances Pteris vittata L. arsenic resistance and accumulation by mediating the rapid reduction and transport of arsenic in roots - Pan, Guofei; Xu, YueZhen; Li, WeiZhen; Zan, Linyan; Wang, Xueli (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) have been widely shown to significantly promote the growth and recovery of Pteris vittata L. growth and repair under arsenic stress; however, little is known about the molecular mechanisms by which AMF mediate the efficient uptake of arsenic in this species. To understand how AMF mediate P. vittata arsenic metabolism under arsenic stress, we performed P. vittata root transcriptome analysis before and after Claroideglomus etunicatum (C. etunicatum) colonization. The results showed that after C. etunicatum colonization, P. vittata showed greater arsenic resistance and enrichment, and its dry weight and arsenic accumulation increased by 2.01–3.36 times. This response is attributed to the rapid reduction and upward translocation of arsenic. C. etunicatum enhances arsenic uptake by mediating the MIP, PHT, and NRT transporter families, while also increasing arsenic reduction (PvACR2 direct reduction and vesicular PvGSTF1 reduction). In addition, it downregulates the expression of ABC and P-type ATPase protein families, which inhibits the compartmentalization of arsenic in the roots and promotes its translocation to the leaves. This study revealed the mechanism of C. etunicatum-mediated arsenic hyperaccumulation in P. vittata, providing guidance for understanding the regulatory mechanism of P. vittata.